POWTOON-BASED MATHEMATICS LEARNING MEDIA: VALIDATION STAGE OF THE PYTHAGOREAN THEOREM - Afif Norma Lidya; Endang Istikomah (UIR PRESS, 2021)
Powtoon is a technology and information (IT)-based learning media, making it easier for students to accept material because of the various animation features and transition effects that make the material easier to understand. This study aims to produce learning media and determine the validity of the Powtoon learning media on the Pythagorean theorem material in class VIII SMP. This type of research is development research. This research goes through potential problems, data collection, product design, design validation, product improvement. The instruments used in this study were material expert assessment sheets and powtoon media. After the powtoon media is created, the powtoon is validated by experts. Validation was carried out by the validator with good scores. The data analysis technique used was validation analysis. From the results of the analysis that had been carried out on the material and media validation sheets, 79% were obtained, which were included in the valid category, namely good. This means that learning media using powtoon can be used